Low literacy Chinese patients: how are they affected and how do they cope with health matters? A qualitative study - Chan YL; Cheng YH; Lam TP (BMC, 2004)
Abstract Background Low literacy is common in Hong Kong and China, especially among the females and the elderly. These are often the patients with the greatest health care needs. However little is known about how low literacy affects the ability of patients to obtain adequate medical care and comply with the recommendations of health professionals. Methods Qualitative study of subjects' opinions using semi-structured group and individual interviews. Thirty-six participants took part in 6 group and 9 individual interviews. Results Participants' opinions towards low literacy were explored in the interviews. They expressed diverse views on how they perceived low literacy. Some thought they were handicapped by it but others felt it was not a problem. Age, gender, chronic illnesses and their attitudes towards self were found to be major factors affecting their perception. Despite their low literacy, some had their specific ways to overcome the difficulties, for example, drawing symbols to help with the timing of taking the medications. Most of them felt better explanation by the health care workers was most important. Conclusions It is highly relevant for health care workers to be aware of the low literacy status of their patients and to explain information so that patients understand it.